The Pioneers Who Set the Foundation for ORNAC - Stephens, Gloria (Operating Room Nurses Association of Canada Journal, 2021)
This article explores the history of perioperative nursing groups that evolved into the Operating Room Nurses Association of Canada. It covers a period of more than 60 years and recognizes the pioneers who helped build the foundation of perioperative nursing organization that exists today. It is written by one of ORNAC’s Past Presidents and incorporates both stories that were shared with her and events that she experienced first-hand.